Legal Approaches to Artificial Intelligence Concept and Essence Definition - Yuryevna Bokovnya, Alexandra (2020)
In this paper, it was tried to provide a comprehensive analysis of the term "artificial intelligence" and its essence definitions existing in the scientific literature. It is noted that nowadays, they developed several approaches to the interpretation of "artificial intelligence" definitions. At the same time, despite a wide range of studies on the interpretation, various areas of application, as well as the legal aspects of "artificial intelligence" concept, the unexplored horizons of this definition are quite wide. For this reason, the level of interest in the multidimensional consideration and analysis of the term "artificial intelligence" is quite high, which allows us to talk about fairly broad prospects for the development of legal approaches to its study.It is shown that the most convincing and consistent position of those scientists who are inclined to describe the concept under consideration by designating its essential properties and signs. These properties and signs of artificial intelligence include the ability to reason and control, legal understanding and legal awareness, learning and development, autonomy and decision making, etc.